Cytotoxic and Antioxidant Activities of Crocus pallasii subsp. haussknechtii Corms Extracts Compared with Crocus sativus - Raheleh Shakeri*; Jalal Khorshidi; Tayebeh Radjabian; Ali Lashkari; Maliheh Safavi (Iranian Society of Pharmacognosy, 2019)
Background and objectives: The goal of this study was to compare the cytotoxic and antioxidant activities of the corms extracts of two Crocus species (C. sativus L. and C. pallasii subsp. haussknechtii). Methods: n-Hexan, chloroform and methanol extracts of the corms were prepared. Cytotoxic activities of the extracts against human breast cancer cell lines MDA-MB-231 and MCF-7 were evaluated via MTT assay and dual acridine orange/ethidium bromide fluorescent staining test. Antioxidant activities of the extracts were assessed by DPPH method. Results: The results showed that the methanol extracts of the corms from both species had cytotoxic activity against the breast cancer cells. Cytotoxic activity of the corms extract of C. sativus L. was significantly higher than C. pallasii subsp. haussknechtii. n-Hexan and chloroform extracts from the corms of C. pallasii subsp. haussknechtii and Crocus sativus L. showed no anti-proliferative activity which indicated the polar nature of the cytotoxic agent(s) in the extracts. The results of dual acridine orange/ethidium bromide fluorescent staining test revealed that the methanol extracts of both species corms destroyed cancer cells through apoptosis. Moreover, the methanol corm extracts of the two species showed little antioxidant activity. Conclusion: It can be concluded that C. sativus L. may possess more significant apoptotic properties compared to C. pallasii subsp. haussknechtii.